Breastfeeding and weaning: a look on the experiences of nurses who are mothers - Bruna Caroline Rodrigues; Sandra Marisa Pelloso; Lais Cristina Rizzato França; Sueli Mutsumi Tsukuda Ichisato; Ieda Harumi Higarashi (Rev Rene)
One aimed to understand the experience of children’s breastfeeding and weaning by nurses who are mothers. Descriptive, exploratory study with a qualitative approach, performed in Maringá, PA, Brazil, with 10 nurses who are mothers, selected by the snowball method between November 2011 and January 2012. Data were collected through semi-structured interviews and analyzed using the content analysis technique. Three categories emerged: understanding the process of pregnancy and breastfeeding in the life context of nurses who are mothers; Outlining the weaning process from the perspective of nurses who are mothers; Breastfeeding and the professional demands of nurses who are mothers: motivations and strategies used for weaning. It was considered that returning to work was the main reason for early weaning, resulting in feelings of frustration by nurses who are mothers for not following the recommendation of exclusive breastfeeding up to the sixth month, in terms of personal experience.